Dissection of physiological, transcriptional, and metabolic traits in two tall fescue genotypes with contrasting drought tolerance. Issue 6 (22nd November 2021) - Kang, Yun; Talukder, Shyamal; An, Zewei; Torres‐Jerez, Ivone; Krom, Nick; Huhman, David; Udvardi, Michael; Saha, Malay C.
Abstract: Tall fescue ( Festuca arundinacea ) is an important cool‐season perennial forage grass that forms mutualistic symbioses with fungal endophytes. Physiological, biochemical and transcriptional comparisons were made between two tall fescue genotypes with contrasting drought tolerance (tolerant, T400, and sensitive, S279), either with or without endophyte ( Epichloë coenophiala ). Drought stress was applied by withholding watering until plants reached mild, moderate and severe stresses. Physiological characterization showed that T400 had narrower, thicker leaves, and lower leaf conductance under well‐watered conditions, compared to S279. After severe drought and recovery, endophytic T400 had greater shoot and root biomass than other plant types. Under drought, leaf osmotic pressure increased much more in T400 than S279, consistent with accumulation of metabolites/osmolytes, especially proline. Gene Ontology enrichment analysis indicated that T400 had more active organic acid metabolism than S279 under drought, and implicated the role of endophyte in stimulating protein metabolism in both genotypes. Overall T400 and S279 responded to endophyte differently in aspects of physiology, gene transcription and metabolites, indicating plant genotype‐specific reactions to endophyte infection.